Acceptability and feasibility of a group intervention for long COVID in Johannesburg, South Africa: a mixed-method study - Ramachandran, Rupa; Sathar, Farzana; Mokome, Pride; Mathabela, Nkululeko; Mahlase, Ency; Charalambous, Salome; Rachow, Andrea; Glover, Nicole Audrey; Ivanova, Olena (Frontiers in Health Services, 2025)
BackgroundCOVID-19 affected 777 million people globally, with 7.1 million deaths. In Africa, 9.6 million cases and 176,000 deaths were reported. Long COVID, a significant consequence of the COVID-19, presented by chronic symptoms, affects the physical and mental health, thereby impacting the quality of life. While high-income countries implemented rehabilitation programs for managing long COVID symptoms, low- and middle-income countries faced healthcare disparities. In South Africa, limited multidisciplinary interventions were evident. This study aimed to assess the acceptability and feasibility of an 8-week rehabilitation and self-management program for long COVID using mixed-methods approach in Johannesburg.MethodsPatients and hospital staff who suffered from at least one symptom of long COVID for a period of two months and who consented to participate in the intervention were recruited from Tembisa Provincial Tertiary Hospital. The recruitment was from July to October 2023. Questionnaires were administered and interviews with selected participants were conducted to assess the acceptability and feasibility of the intervention. A descriptive analysis was carried out for the quantitative data, and a deductive thematic analysis was used for the interviews.ResultsThe participants had positive perceptions towards the design of the intervention, delivery, materials used and support by research staff and external consultants such as dietitians, physiotherapists, and psychologists. The participants stated that the intervention had improved their knowledge of long COVID and increased their self-confidence. Major barriers related to the intervention perceived by the participants were infrastructure, time and language. Recommendations from the participants included expanding the intervention at the community level and extending the duration of the intervention beyond 8-weeks.ConclusionThis pilot intervention, that aimed to manage the symptoms of long COVID, was well accepted by the participants and achieved its intended outcome. Similar interventions are required at the clinical as well as community levels.